Complex mathematical modeling of heat pump power supply based on wind-solar network electrical system - Chaikovskaya, Eugene (Technology audit and production reserves, 2020)
The object of research is to support the functioning of a heat pump power supply based on a grid-type wind-solar electric system using hybrid solar collectors. One of the most problematic areas is the harmonization of energy production and consumption in the context of distributed energy generation using renewable sources. Connecting to Smart Grid technologies will prevent the peak load of the power system in conditions of voltage regulation when connecting the heat pump power supply. An integrated system has been developed to support the operation of heat pump power supply based on predicting changes in the temperature of local water when measuring voltage from hybrid solar collectors at the input to the grid inverter, voltage at the output of the frequency converter and voltage frequency. The adoption of advanced decisions to maintain the temperature of local water by changing the power of the electric motor of the heat pump compressor is based on establishing the ratio of the voltage at the input to the grid inverter and the voltage at the output of the frequency converter are measured. The change in the refrigerant flow rate according to the frequency control of the electric motor of the heat pump compressor occurs in accordance with the change in the thermal power of the low-potential energy source – the lower section of the two-section storage tank connected to hybrid solar collectors. The architecture, the mathematical substantiation of the architecture of the technological system, the mathematical substantiation of supporting the functioning of the heat pump power supply are proposed. The basis of the technological system is a dynamic subsystem, which includes the following components: wind power plants, photovoltaic solar panels, hybrid solar collectors, grid inverter, two-section storage tank, heat pump, frequency converter. The operating parameters of the heat pump system, the parameters of heat exchange in the condenser of the heat pump, the time constants and coefficients of the mathematical model of the dynamics of the temperature of local water for the established levels of functioning are determined according to the coordination of production and consumption of energy.